A guide to novice for proper selection of the components of drone for specific applications. (2022) - N.C., Ajay Vishwath; Yadav, Arvind R; Mehta, Deep; Belani, Jatin; Raj Chauhan, Ravi
Abstract: Since the introduction of drone technology, it has caught the attention of researchers across the world for utilizing it in different areas. But as it is known the same drone cannot be used for all the applications as each and every application has its own unique challenges and requirements. The existing literature emphasizes the use of sophisticated drones for certain applications. But if a novice wants to prepare a tailor made drone for a specific application it is a difficult task for them. This work is an attempt to address the challenges and requirements of drones namely for, agriculture, healthcare, firefighting, and food delivery applications. Which in turn shall be helpful in identifying the right components required for an application? It begins with the statement of various applications of drones and thereby defining the requirements for each application. As per the requirements vigorous calculations are imparted to choose the right combination of electronic components keeping minimal cost in mind. This work could guide any amateur drone enthusiasts to proceed with making their own drone for recreational or commercial purposes. Even the drone entrepreneurs can build their enterprise just by using the output of this manuscript with their expertise or research and development team through proper unmanned vehicle lab facilities.